Rheological and mechanical properties of alginate gels and films containing different chelators. (April 2020) - Hilbig, Jonas; Hartlieb, Katrin; Gibis, Monika; Herrmann, Kurt; Weiss, Jochen
Abstract: The application of co-extruded calcium alginate casings is becoming more and more popular for the production of dry fermented sausages with small caliber. However, the formation of white efflorescence in coextruded sausages is a substantial problem for manufacturers. Previous studies had shown though that addition of chelators can inhibit formation of efflorescences in non-coextruded sausages. Effect of addition of such compounds to alginate gels used for formation of casings in the co-extrusion technology is yet unknown. Therefore, the influence of calcium chloride (crosslinking solution) and various chelators on the properties of the alginate gels and casings were investigated. The study showed that the influence of increasing concentrations of CaCl2 in the crosslinking solution is of minor importance for the stability of the casings. However, depending on the chelator the stability was either increased, decreased or the same as the control. The addition of citrate did not change the properties, the addition of the polyphosphate P69 significantly increased ( p < 0.05 ) the tensile strength and elastic modulus by 20.84% and 66.54%, respectively. Whereas, the addition of citric acid (68.05% and 63.10%) and the mixture of di- and polyphosphate TARI S78 (26.16% and 13.65%) significantly decreased ( p < 0.05 ) the tensile strength and elastic modulus of the casing. The study showed that the influence of chelators on the alginate gel have to be investigated before the application and furthermore the strengthening could lead to new applications of the casings. Graphical abstract: Image 10790 Highlights: Alginate casings were produced with the addition of different chelators. Concentration of CaCl2 of minor importance for the stability of the casings. The rheological properties were influenced differently by the chelators. Increase or decrease of casing stability were possible by the addition.